Bibliography and the sociology of texts - McKenzie, D. F. (Donald Francis) (Panizzi lectures ;, 1999)
In Bibliography and the Sociology of Texts, D.F. McKenzie shows how the material form of texts crucially determines their meanings. He unifies the principal interests of both critical theory and textual scholarship to demonstrate that, as all works of lasting value are reproduced, re-edited and re-read, they take on different forms and meanings. By witnessing the new needs of their new readers these new forms constitute vital evidence for any history of reading. McKenzie shows this is true of all forms of recorded information, including sound, graphics, films, representations of landscape and the new electronic media. The bibliographical skills first developed for manuscripts and books can, he shows, be applied to a wide range of cultural documents. This book, which incorporates McKenzie's classic work on orality and literacy in early New Zealand, offers a unifying concept of texts that seeks to acknowledge their variety and the complexity of their relationships.